The Significance of Workforce Diversity on Employee Performance at the Regional Secretariat Office of Gowa Regency - Ernol, Ernol; Muhammad Ikram Idrus; M. Yusuf Alfian Rendra Anggoro (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
In today’s dynamic organizational environment, workforce diversity has become a critical factor influencing employee performance and overall institutional effectiveness. This research is a quantitative study aimed at determining the significance of workforce diversity on employee performance at the Gowa Regency Secretariat. The research sample consisted of employees of the Gowa Regency Secretariat. The type of data used is quantitative data obtained through the distribution of questionnaires and adjusted to the issues being studied. Data collection techniques were carried out through questionnaires, observation, and documentation. The data sources used included primary and secondary data. The research instrument employed the Likert scale method. Based on data processing results using statistical calculations through the Statistical Package for the Social Sciences (SPSS) version 25 regarding the significance of workforce diversity on employee performance at the Gowa Regency Secretariat, as discussed in the previous chapter, the author concludes that workforce diversity has a positive and significant effect on employee performance at the Gowa Regency Secretariat.